O preenchimento e o apagamento do pronome sujeito de 1ª pessoa do singular: uma análise variacionista no falar fortalezense - Pinto Júnior, Clealdo (2020)
The Brazilian Portuguese pronominal paradigm undergoes profound changes, associated with a morphological simplification of the flexional nucleus. Several researches (Galves, 2018; Marinho, 1996) attest to a greater filling in the subject pronoun in Brazilian Portuguese, differentiating it from other pro-drop languages (Chomsky, 1981). This work sought to describe the variable use of the expression form of the subject pronoun of the 1st person singular in the database of NORPOFOR (Norma Oral do Português Popular de Fortaleza, Oral Norm of Portuguese Popular of Fortaleza), in which the variant forms filling in and erasing the subject compete for space in the speech of the community. Thus, based on the assumptions of Variationist Sociolinguistics (Labov, [1972] 2008; 2001; Weinreich; Herzog; Labov, [1968] 2006), as well as in research by Duarte (1995; 2003), Galves ([1983] 2018 ), Marinho (1996), among others, sought to verify whether linguistic factors (time / verbal mode and nominal forms, type of sentence and presence of elements on the left) and extralinguistic factors (gender, education and age group) condition the filling in the subject pronoun of 1st person singular. The corpus of this research has 24 surveys, stratified according to the social variables gender, age group (15-25; 26-49 and 50 years onwards) and education (0-4 and 9-11 education). Such surveys come from the NORPOFOR database, selected from the interviews that make up the one-on-one tape-recorded conversational interview (Labov 1972, 1984; Wolfram and Fasold, 1974). The data selected in the surveys were submitted to the Goldvarb X statistical program (Sankoff, Tagliamonte, and Smith, 2005), which allows the identification of significant factors for the variable phenomenon under study, by calculating frequencies and Relative Weights. Thus, it was found that the variable “form of expression of the subject pronoun of 1st person singular” is stable (Labov, 2008) in the popular saying of Fortaleza, showing a significant favoring of the variant filling in the subject pronoun (64.1 % fill). The groups of linguistic factors elements on the left, type of sentence and verb tense / mode and nominal forms exercise a conditioning of the variable under study. As for social factors, the variables gender and age group were selected by Goldvarb X, demonstrating a social conditioning in the use of the variable. Therefore, the popular speech of Fortaleza presents a higher frequency of filling in the pronoun subject of 1st person singular due to changes in the verbal paradigm, as well as by the linguistic and social conditioning of the variable.